Markor: A Measure of Market Orientation - Kohli, Ajay K.; Jaworski, Bernard J.; Kumar, Ajith (Journal of Marketing Research, 1993)
In recent years, academic and practitioner interest has focused on market orientation and factors that engender this orientation in organizations. However, much less attention has been devoted to developing a valid measure of market orientation. Here we define market orientation as the organizationwide generation of market intelligence pertaining to current and future needs of customers, dissemination of intelligence horizontally and vertically within the organization, and organization-wide action or responsiveness to market intelligence. The authors describe a procedure to develop a measure of the construct. Key features of the research methodology include several rounds of pretesting, a single-informant assessment, and a multi-informant (both marketing and nonmarketing executives) replication and extension. The multi-informant results indicate that the proposed 20-item market orientation scale (MARKOR) may be best represented by a factor structure that consists of one general market orientation factor, one factor for intelligence generation, one factor for dissemination and responsiveness, one marketing informant factor, and one nonmarketing informant factor. Taking into account the informant factors, the subsequent validation tests are moderately supportive of the market orientation construct. The authors discuss methodological, substantive, and application directions for future research in light of these findings.